Testing System for PV Grid-Connected Power Condition Systems with Support for Ancillary Services - Pires, Vítor Fernão (2023)
Funding Information: This work was supported by national funds through FCT—Fundação para a Ciência e a Tecnologia with reference UID/CEC/50021/2020 and UID/EEA/00066/2020. Publisher Copyright: © 2023 by the authors.